2019
DOI: 10.1097/qai.0000000000002183
|View full text |Cite
|
Sign up to set email alerts
|

Benzodiazepine Use Is Associated With an Increased Risk of Neurocognitive Impairment in People Living With HIV

Abstract: Objective: Despite potential for dependence and adverse neurological effects, long-term benzodiazepine (BZD) use is common among people living with HIV (PLWH). As PLWH are at risk for central nervous system dysfunction, we retrospectively examined the association between BZD use and HIV-associated neurocognitive impairment (NCI). Methods: Three hundred six PLWH underwent comprehensive neurobehavioral evaluations. Current BZD use (BZD+) was determined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 49 publications
3
6
0
Order By: Relevance
“…In contrast, benzodiazepine groups were comparable in rates of current and past substance use disorders and in HIV disease characteristics with the exception of a longer duration of HIV disease in benzodiazepine users versus non-users. Consistent with our previous results in a sample of PWH with and without viral suppression (Saloner et al 2019b ), we found higher rates of NCI in benzodiazepine users (49.3%) versus non-users (36.1%) ( X 2 = 4.86, p = 0.03) among ART-treated, virally suppressed PWH. Among considered covariates, BDI-II scores, lifetime MDD diagnosis, number of medications, antidepressant and antipsychotic medication use and current alcohol use disorder were associated with NCI at p ≤ 0.10 and, thus, were included in all statistical models.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…In contrast, benzodiazepine groups were comparable in rates of current and past substance use disorders and in HIV disease characteristics with the exception of a longer duration of HIV disease in benzodiazepine users versus non-users. Consistent with our previous results in a sample of PWH with and without viral suppression (Saloner et al 2019b ), we found higher rates of NCI in benzodiazepine users (49.3%) versus non-users (36.1%) ( X 2 = 4.86, p = 0.03) among ART-treated, virally suppressed PWH. Among considered covariates, BDI-II scores, lifetime MDD diagnosis, number of medications, antidepressant and antipsychotic medication use and current alcohol use disorder were associated with NCI at p ≤ 0.10 and, thus, were included in all statistical models.…”
Section: Resultssupporting
confidence: 92%
“…Domain-specific analyses showed that the benzodiazepine use X medical burden interaction was evident in speed of information processing, verbal fluency and motor function. This is consistent with our prior study that also found an adverse effect of benzodiazepine use on speed of information processing and motor domains among PWH (Saloner et al 2019b ). A commonality among speed of information processing, motor function, and verbal fluency is that they are all speed-dependent and regulated by frontostriatal neural circuitry (Ances et al 2012 ; Hakkers et al 2017 ), which aligns with the theory that benzodiazepine causes psychomotor slowing (Rollings et al 1994 ; Stewart 2005 ; Lader 2011 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“… 7 This was further highlighted by Rowan et al who proposed an increased risk in neurocognitive impairment in people living with HIV (PLWH) who use benzodiazepines. 8 …”
Section: Introductionmentioning
confidence: 99%
“…7 This was further highlighted by Rowan et al who proposed an increased risk in neurocognitive impairment in people living with HIV (PLWH) who use benzodiazepines. 8 A United States of America study highlighted that chronic benzodiazepine users are estimated at 500 000 to 1 million in the United Kingdom, 4 million in the United States of America and several Background: Benzodiazepines are often used as a part of mental health pharmacological management; however, often when prescribed for extended periods, they increase the risk of benzodiazepine use disorder (BUD). Clinical interviews are at the centre of diagnosing this disorder.…”
mentioning
confidence: 99%